ANALYSIS OF CUSTOMER SATISFACTION INDEX METHOD ON THE PERCEPTION OF UNIVERSITAS PRIMA INDONESIA'S NEW BUILDING BY ITS STUDENTS - Nasution, Donni; Sinaga, Aldi Hermanto; Samudera , Indra; Hulu, Iman Paskalis (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The rapid growth of private universities and higher education institutions has led to increased competition among faculties to meet their set quotas, resulting in uneven student distribution. Universities and faculties must consistently strive to improve quality in various areas to achieve their set quotas. In measuring student satisfaction, a questionnaire was distributed to students. Out of the 369 questionnaires filled out, only 235 were deemed valid and analyzed. The analysis was conducted using two calculation methods, the first being the Customer Satisfaction Index (IPA), which resulted in a 75.42% satisfaction rate, and the Importance Performance Analysis (IPA), which identified 10 indicators in quadrant 1. It can be said that both methods resulted in a fairly satisfactory service quality.